2003
DOI: 10.1081/sl-120024580
|View full text |Cite
|
Sign up to set email alerts
|

A Power Interruption Technique for Determining the Difference Between Electron and Gas Temperatures in the Argon d.c. Arc Supplied with Aqueous Aerosol

Abstract: The difference between electron and gas temperatures in a low current U-shaped d.c. arc with aqueous aerosol supply was studied using a power interruption technique. Monitoring of the temporal evolution of recombination continuum after power switch-off revealed that it was necessary to do a correction of the measured values due to a change in electron concentration. It was shown that the plasma studied was a two temperature type and that the temperature difference ranges from 1850 K to 600 K for arc currents f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Therefore, studied plasma is not in the LTE state but gradually approaches that state with increasing current: the difference between variously defined temperatures is reduced with electron number density increase. By comparing these results with the previously published, [8] obtained using the same arc device but with water aerosol introduction, it may be concluded that water aerosol increases kinetic energy transfer efficiency, i.e. reduces T e − T h difference and brings plasma closer to the LTE state.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Therefore, studied plasma is not in the LTE state but gradually approaches that state with increasing current: the difference between variously defined temperatures is reduced with electron number density increase. By comparing these results with the previously published, [8] obtained using the same arc device but with water aerosol introduction, it may be concluded that water aerosol increases kinetic energy transfer efficiency, i.e. reduces T e − T h difference and brings plasma closer to the LTE state.…”
supporting
confidence: 59%
“…Rough comparison of our previous results for argon plasma with aerosol introduction. [8] with the results for pure argon arc plasma. [1,2] has shown that this influence manifests itself in substantial decrease of the difference between T e and T h .…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…For heavy particle temperature T h evaluation we have used a power interruption method [29][30][31]. From the measured temporal evolutions of argon spectral lines after power switchoff we have obtained the ratio of the spectral line intensities before (I 0 ) and after (I ) the interruption.…”
Section: Temperature Measurementsmentioning
confidence: 99%
“…Also, the relatively long horizontal part of the arc column makes it suitable for atomic absorption measurements, especially for elements that form refractory oxides [13]. In this source, fast responses of spectral line intensities to power interruption were studied for a number of atomic species, to get a better insight into the different excitation mechanisms that occur in the arc plasma [14], and also to get information regarding the state of thermodynamic equilibrium [15][16][17]. A power modulation method was used to investigate delayed responses of argon and hydrogen spectral lines and also of continuum radiation [18].…”
Section: Introductionmentioning
confidence: 99%